Complete Genome Sequence of the Model Rhizosphere Strain Azospirillum brasilense Az39, Successfully Applied in Agriculture - Rivera Botia, Diego Mauricio (2014)
We present the complete genome sequence of Azospirillum brasilense Az39, isolated from wheat roots in the central region of Argentina and used as inoculant in extensive and intensive agriculture during the last four decades. The genome consists of 7.39 Mb, distributed in six replicons: one chromosome, three chromids, and two plasmids.